Gk with derek the ultimate general knowledge and quiz compendium: 4 india - O'Brien, Derek (Penguin Books, 2004)
Gk with derek the ultimate general knowledge and quiz compendium: 4 india / O'Brien, Derek. -- New Delhi: Penguin Books, 2004 001 Obr13 v4 No. of Copies : 2